An eye-tracking study on visual perception of vegetation permeability in virtual reality forest exposure - Li, Chang; Du, Chunlan; Ge, Shutong; Tong, Tong (Frontiers in Public Health, 2023)
Previous studies have confirmed the significant effects of single forest stand attributes, such as forest type (FT), understory vegetation cover (UVC), and understory vegetation height (UVH) on visitors' visual perception. However, rarely study has yet clearly determined the relationship between vegetation permeability and visual perception, while the former is formed by the interaction of multiple forest stand attributes (i.e., FT, UVC, UVH). Based on a mixed factor matrix of FT (i.e., coniferous forests and broadleaf), UVC level (i.e., 10%, 60%, and 100%), and UVH level (1m, 1m, and 3m), the study creates 18 immersive virtual forest videos with different stand attributes. Virtual reality eye-tracking technology and questionnaires are used to collect visual perception data from viewing virtual forest videos. The study finds that vegetation permeability which is formed by the interaction effect of canopy density (i.e., FT) and understory density (i.e., UVC, UVH), significantly affects participant’s visual perception: in terms of visual physiology characteristics, pupil size is significantly negatively correlated with vegetation permeability when participants are viewing virtual reality forest; in terms of visual psychological characteristics, the understory density formed by the interaction of UVC and UVH has a significant impact on visual attractiveness and perceived safety and the impact in which understory density is significantly negatively correlated with per-ceived safety. Apart from these, the study finds a significant negative correlation between average pupil diameter and perceived safety when participants are viewing virtual reality forests. The findings may be beneficial for the maintenance and management of forest parks, as well as provide insights into similar studies to explore urban public green spaces.